Research on Partial Least Squares Method Based on Deep Confidence Network in Traditional Chinese Medicine - Wang-ping Xiong; Tian-ci Li; Qing-xia Zeng; Jian-qiang Du; Bin Nie; Chih-Cheng Chen; Xian Zhou (Discrete Dynamics in Nature and Society)
Partial least squares method has many advantages in multivariate linear regression modeling, but its internal cross-checking method will lead to a sharp reduction of the principal component, thereby reducing the accuracy of the regression equation, and the selection of principal components about the traditional Chinese medicine data is particularly sensitive. This paper proposes a kind of partial least squares method based on deep belief nets. This method mainly uses the deep learning model to extract the upper-level features of the original data, putting the extracted features into the partial least squares model for multiple linear regression and evading the problem that selects the number of principal components, continuously adjusting the model parameters until satisfied well-pleased accuracy condition. Using Dachengqitang experimental data and data sets in the UCI Machine Learning Repository, the experimental results show that the partial least squares analysis method based on deep belief nets has good adaptability to TCM data.